Pashtun Neo-Ethnonationalism - Amin, Husnul (The review of faith & international affairs, 2023)
The aim of this paper is threefold. Firstly, it seeks to examine the genesis and widespread adoption of a more inclusive and expansive political trend known as Pashtun neo-ethnonationalism in Pakistan. Secondly, it aims to investigate the various dimensions, trajectories, and growing influence of neo-ethnonationalism among diverse social forces, including left-leaning groups, Islamists, developmentalists, modern professionals, and others. Lastly, the paper aims to discuss the key factors and dynamics that have contributed to the emergence and proliferation of neo-nationalism within the diverse Pashtun social fabric. Contrary to stereotypical assumptions that depict Pashtun nationalist expression as static and primordial and characterized by violence and conflict, this research delves into the dynamics of ruptures, negotiations, and assimilations that shape the evolving neo-Pashtun identity.